2009
DOI: 10.4049/jimmunol.0803624
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived Proteinase 3 Induces Kallikrein-Independent Release of a Novel Vasoactive Kinin

Abstract: The kinin-forming pathway is activated on endothelial cells and neutrophils when high-molecular weight kininogen (HK) is cleaved by plasma kallikrein liberating bradykinin, a potent mediator of inflammation. Kinins are released during inflammatory conditions such as vasculitis, associated with neutrophil influx around blood vessels. Some patients with vasculitis have elevated plasma levels of neutrophil-derived proteinase 3 (PR3) and anti-PR3 Abs. This study investigated if neutrophil-derived PR3 could induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 41 publications
(46 reference statements)
3
68
0
Order By: Relevance
“…The affinity of the PR3 kinin is marginally better at B 1 receptors (Fig. 1A), but not as strong as previously reported by Kahn et al [2]. Further, these authors reported that Met-Lys-BK-Ser-Ser activated phospholipase C in cells only at 1 µM, at variance with their own binding results, but possibly consistent with our affinity findings.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The affinity of the PR3 kinin is marginally better at B 1 receptors (Fig. 1A), but not as strong as previously reported by Kahn et al [2]. Further, these authors reported that Met-Lys-BK-Ser-Ser activated phospholipase C in cells only at 1 µM, at variance with their own binding results, but possibly consistent with our affinity findings.…”
Section: Discussionsupporting
confidence: 92%
“…1B; table 1), as previously reported [2]. The affinity of the PR3 kinin is marginally better at B 1 receptors (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations